Daily field checking list by Walter Rosene, May 14, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 14, 1936. This checklist was used by Walter Rosene to record birds sighted around Heitkamp Ponds and North Bridge between 6:00 and 9:00. Plustek--flatbed